2000
DOI: 10.4315/0362-028x-63.4.479
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Enterotoxins and Toxic Shock Syndrome Toxin Genes in Staphylococcus aureus by Polymerase Chain Reaction

Abstract: A simple polymerase chain reaction (PCR)-based procedure was developed for the detection of fragments of staphylococcal enterotoxins (SEs) SEA, SEB, SEC, SED, SEE, SEG, SEH, and SEI together with the toxic shock syndrome toxin (TSST-1) genes of Staphylococcus aureus. One hundred and twenty-nine cultures of S. aureus were selected, 39 of which were recovered from 38 suspected staphylococcal food-poisoning incidents. The method was reproducible, and 32 different toxin genotypes were recognized. The presence of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(134 citation statements)
references
References 17 publications
7
123
0
4
Order By: Relevance
“…The lack of correlation between the results from biochemical and molecular assays have already been observed in the literature (McLAUCHLIN et al, 2000;ROSEC;GIGAUD, 2002;JØRGENSEN et al, 2005). Jørgensen et al (2005) and Kérouanton et al (2007) suggested the possibility of variations in the sequences of the analyzed genes, which could hinder the proper annealing of the primers in the PCR reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of correlation between the results from biochemical and molecular assays have already been observed in the literature (McLAUCHLIN et al, 2000;ROSEC;GIGAUD, 2002;JØRGENSEN et al, 2005). Jørgensen et al (2005) and Kérouanton et al (2007) suggested the possibility of variations in the sequences of the analyzed genes, which could hinder the proper annealing of the primers in the PCR reaction.…”
Section: Discussionmentioning
confidence: 99%
“…additional differences in the genes that would be present in the isolates. McLauchlin et al (2000) considered that the degree of homology between the enterotoxins, especially the less studied non-classical ones, could generate cross-immune reactions and generate false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, reports have been produced for the identification of the toxin gene using PCR methods (28,41,42). However, these methods could not be applied when the bacteria have not already existed in specimens sterilized.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion results in nausea, vomiting and diarrhoea while inhalation provokes non-productive cough, chest pain and dyspnea. Classical ways of detection are mainly based on multiplex PCR (McLauchlin et al 2000;Mehrotra et al 2000) and immunoassays (Freed et al 1982;Wieneke 1991), which allow quantitative or qualitative measurements in less than 24 hours. A peptide displaying-phage for the optical detection of SEB with biosensor technology was developed by Goldman et al (2000).…”
Section: Detection Of Staphylococcal Enterotoxin B (Seb)mentioning
confidence: 99%